Quantifying the impact of red tape on investment: A survey date approach - Bruno Pellegrino; Geoffery Zheng (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2023)
An important strand of research in macro-finance investigates which factors impede enterprise investment, and what is their aggregate economic cost. In this paper, we make two contributions to this literature. The first contribution is methodological: we introduce a novel framework to calibrate macroeconomic models with firm-level distortions using enterprise survey micro-data. The core of our innovation is to explicitly model the firms' decisions to report in the survey the distortions they face. Our second contribution is to apply our method across seven countries to characterize the distribution of these distortions and estimate the gross domestic product (GDP) loss induced by distortionary red tape. Our estimates are based on a dynamic general equilibrium model with heterogeneous firms whose capital investment decisions are distorted by red tape. We find that the aggregate cost of red tape varies widely across the countries in our dataset, with an average cost of 0.8% of annual GDP. Our framework opens up a new range of applications for enterprise surveys in macro-financial modeling and policy analysis.
Keywords: C83; E2; E6; G38; H1; H2; K2; O1; O4; 330; Bureaucracy; Growth; Investment; Legislation; Misallocation; Red Tape; Regulations; Survey